Isotopic niche modelling of the Pondaung mammal fauna (middle Eocene, Myanmar) shows microhabitat differences. Insights into paleoecology and early anthropoid primate habitats - Habinger, Sophie G.; Chavasseau, Olivier; Ducrocq, Stéphane; Chaimanee, Yaowalak; Jaeger, Jean-Jacques; Sein, Chit; Soe, Aung Naing; Stern, Samuel; Bocherens, Hervé (Frontiers in Ecology and Evolution, 2023)
The late Middle Eocene Pondaung Fm. is a window to understand the environment and ecosystem dynamics of a past greenhouse world and the paleoenvironments where modern mammal clades such as anthropoid primates originated. Previous studies focused on the overall climate and vegetation of this Eocene habitat and provided first evidence for an early monsoon onset before the orogenesis of the Himalayan-Tibetan range. Here, we wanted to investigate how the mammal fauna used this habitat and which different ecological niches and microhabitats they occupied. We analyzed the carbonate fraction of dental enamel of a fossil mammal assemblage from various localities of the Pondaung Fm. in Myanmar. Bayesian niche modelling of the δ13C and δ18O values allowed us to quantify aspects of the ecological core niches occupied by these taxa, to calculate niche overlap and to use these data to infer directional competition potential in this mammal assemblage. Furthermore, comparison of different areas of the Pondaung Fm. revealed two different microhabitats whose distribution is consistent with existing vegetation models. Most primate taxa were found in both described environments, which gives a first indication about their ecological flexibility.